Study of Students’ Vocabulary Difficulties in Third-Semester Students of Food Technology Major - Juliana Sujadi; Fariska Wulandari (Edukasi: Jurnal Pendidikan, 2021)
AbstractThis research aimed to know the students’ vocabulary ability and difficulties in learning vocabulary. The subject of the research was the third-semester students of Food Technology. The method used in this research is descriptive qualitative with questionnaire and interview as the instruments of data collecting. The data was analyzed qualitatively with the process of data collection, data reduction, and data display/conclusion drawing. The result of the research showed the students still have low vocabulary ability and there are some vocabulary difficulties experienced by the students, they have a very limited number of vocabularies; mispronounce English words; spelling English words especially for ‘a’, ‘I’, and ‘e’; do not understand long and complex words such as public health center, expired date, and fish spoilage. The students also have problems with range, connotation, and idiom in English. AbstrakPenelitian bertujuan untuk mengetahui kemampuan kosakata dan kesulitan mahasiswa dalam belajar kosakata bahasa Inggris. Subjek penelitian adalah mahasiswa semester tiga Jurusan Teknologi Pangan. Metode penelitian menggunakan deskriptif kualitatif dengan kuesioner dan wawancara sebagai instrumen pengumpulan data. Data hasil penelitian dianalisis secara kualitatif dengan tahap pengumpulan data, pengurangan data, dan penarikan kesimpulan. Hasil penelitian menunjukkan mahasiswa semester tiga Jurusan Teknologi Pangan Politeknik Tonggak Equator memiliki kemampuan kosakata bahasa Inggris yang rendah dan terdapat beberapa kesulitan belajar kosakata yang dihadapi yaitu memiliki pembendaharaan kosakata bahasa Inggris yang rendah, memiliki kesulitan dalam pelafalan dan pengejaan ‘a’, ‘I’, dan ‘e’, tidak mengerti kosakata yang panjang dan rumit, memiliki masalah dengan penerjemahan. Mahasiswa juga memiliki masalah dengan penyusunan kata, konotasi, dan idiom dalam Bahasa Inggris.